Experimental study on low recycling no-ELM high confinement mode in EAST. (5th July 2019) - Ye, Y.; Xu, G.S.; Wang, Y.F.; Lin, X.; Guo, H.Y.; Chen, R.; Yan, N.; Zhang, T.; Zhou, C.; Xu, J.C.; Hu, J.S.; Sun, Z.; et al.
Abstract: A highly reproducible spontaneous non-inductive low recycling no-ELM regime has been achieved in the EAST superconducting tokamak with the water-cooled tungsten divertor and molybdenum first wall. The salient feature is that after the L-H transition, emission intensity, divertor neutral pressure and the separatrix electron density all decrease, and the amplitude of ELMs decreases simultaneously until they disappear completely. This scenario exhibits a distinct density threshold, which is dependent on plasma current and wall condition. ELITE/NIMROD simulations indicate that the density at the foot of pedestal and ion diamagnetic effect may play a key role in the achievement of no-ELM operation; the low pedestal foot density might have a strong ion diamagnetic stabilizing effect, which can stabilize the medium- n and high- n Peeling-Ballooning modes. In order to achieve this low pedestal foot density condition, a number of techniques have been employed in EAST, i.e. through extensive lithium wall conditioning and active control of plasma configuration and strike point position. The low recycling no-ELM regime can be extended into a small ELMs regime by increasing the pedestal foot density to facilitate impurity control for long pulse operation, which has been demonstrated in EAST with a pulse length exceeding 101 s. Such a small ELMs regime provide a possible approach toward long-pulse steady-state H-mode operation in future devices.